MOLECULAR DESIGN AND SYNTHESIS OF PIPERAZINEDIIUM DUAL CHARGE CATION IONIC LIQUIDS FOR C02 CAPTURE - ABDELGADIR, OMER EISA BABIKER (2016)
Rapid increases in the concentrations of atmospheric carbon dioxide (COz) which has been linked with global climate change, has motivated scientists and researchers to find various solutions to reduce this emission. Numerous conventional adsorbent used in C02 capture technologies; however, have several performance disadvantages such as low adsorption capacity, limited cycle lifetime and poor stability in multi-cycle operations. Ionic liquids (ILs) sorbent with its unique properties could achieve excellent COz capture performance by introducing selective functions to the cations and anions. The performance of !Ls in capturing COz could be enhanced by designing multi-charged cations. This work presents the development of a new series of piperazinediium dual-charged cation ionic liquids (DCC!Ls). The development of DCC!Ls consists of firstly, molecular design and simulation, secondly synthesis and characterization, and finally, C02 capture performance analysis.